Race, Ethnicity and Gender in Education
XXII, 230 p.
Keywords: This, the sixth volume in Springer’s Globalisation, Comparative Education and Policy Research series, presents scholarly research on major discourses of race, ethnicity and gender in education. It is a sourcebook of ideas for researchers, practitioners and policy makers in education, globalisation, social justice, equity and access in schooling around the world. The aim of the book is to provide an easily accessible, practical yet scholarly source of information about issues of international concern in the field of globalisation and comparative education. Readers will also find here the very latest thinking on race, ethnicity and gender in the context of global culture. Editors Zajda and Freeman have compiled perspectives on education and policy research that are relevant to progressive pedagogy, social change and transformational educational reforms in the 21st century. The book critically examines the interplay between state, ideology and current discourses of race, ethnicity and gender in the global culture. It draws on recent research in the areas of globalisation, equity, social justice, and the role of the State. The authors also explore conceptual frameworks and methodological approaches that could be applied to research covering the State, globalisation, race, ethnicity and gender, and analyze existing inequalities due to race, ethnicity and gender and resultant social stratification. Finally, the book demonstrates the neo-liberal ideological imperatives of education and policy reform, affecting race, ethnicity and gender, and illustrates the way the relationship between the State and education policy affects current trends in education policy as well as reforms in the fields of race, ethnicity and gender.